(untitled) (Лучшие интеллектуальные исследования, 2024)
Annotation: This paper aims to verify these claims and confirm the effectiveness of using songs as a means to improve young learners’ English language vocabulary and to determine whether songs influence young learners’ motivation to learn English. The paper deals with theoretical explanations of young learners, listening skills, and different aspects of using and teaching songs.